Viabilidade econômica de produção de etanol a partir de descarte de batata-inglesa - DELPONTE, ANGELO ANTONIO (2018)
Economic and mainly environmental factors drive the production of biofuels worldwide. Brazil, a major technology provider for the production of ethanol from sugarcane, is already an established biofuel and replaces and is added (30% of the total) in gasoline, representing a good percentage of the total energy needed to transport. This factor is important for regions where there is sugar cane cultivation, which is not the case in the region of Guarapuava-PR and much of the south of the country. This scenario demonstrates an opportunity to increase the variety of raw materials for local ethanol production. In order to do so, the viability of production and the cost of potatoes for the production of ethanol were analyzed, and within this research it was established that up to 35% of the total potatoes harvested are considered as refuse which is unfit for consumption . Therefore this product that when done its correct disposal generates costs for the producer, then the use of this by-product previously considered as "waste" is seen with good eyes. By using and adding value to a product that was previously considered "waste", the present work sought to evaluate the viability of ethanol production from the potato scrap in the region of Guarapuava-PR, which has a large production of this product in a model of micro plants (capacity 2,100 L.dia). Within the viability of ethanol production of the refuse of the potato, the same happened as profitable and lucrative since the cost of the raw material is near 0 and the return of the invested capital is given superior to the Selic rate.